Comparación De Los Dos Diferentes Tipos De Congelación En Equinos (Mografia) (2023)
Cryopreservation has positioned itself as an excellent method in the equine industry thanks to the fact that it favors genetic improvement. (Peña et al., 2011). For this reason, various studies are carried out, with the objective of perfecting biotechnology focused on reproduction, among them semen freezing and artificial insemination (Medeiros et al 2002).